Microstructure and Properties of Insitu TiAl3 Particlereinforced Aluminum Matrix Composites - QIN Jin; CHEN Gang; DU Zhi ming; LIU Xiao jing (Journal of Harbin University of Science and Technology)
TiAl3/2024Al composites were prepared by ultrasonicassisted insitu casting.The microstructures, mechanical properties and wear resistance of TiAl3/2024Al composites were studied. The results of XRD analysis show that TiAl3 is the only product obtained by adding Ti particles into 2024Al melt with ultrasonic stirring at 835℃ for 15min. SEM observation showed that the introduction of highintensity ultrasonic destroyed the directional growth trend of TiAl3 phase, and TiAl3 reinforcement with fine particles and uniform distribution in the matrix was obtained. Compared with 2024Al treated by ultrasonic, the Vickers hardness of 14vol.%TiAl3/2024Al composite matrix increased by 43%, the yield strength and tensile strength of the composite increased by 34% and 19%, respectively. Friction and wear experiments show that 2024Al wears seriously after 30 minutes testing, while 14vol.%TiAl3/2024Al composites wear less, which indicates that the insitu TiAl3 particles can significantly improve the wear resistance of materials.